Endoplasmic reticulum stress targeted therapy for breast cancer - Di Xu; Zhen Liu; Ming-Xing Liang; Yin-Jiao Fei; Wei Zhang; Yang Wu; Jin-Hai Tang (Cell Communication and Signaling, 2022)
Abstract Recurrence, metastasis, and drug resistance are still big challenges in breast cancer therapy. Internal and external stresses have been proven to substantially facilitate breast cancer progression through molecular and systemic mechanisms. For example, endoplasmic reticulum stress (ERS) results in activation of the unfolded protein response (UPR), which are considered an important cellular stress response. More and more reports indicate its key role in protein homeostasis and other diverse functions involved in the process of breast cancer progression. Therefore, therapies targeting the activation of ERS and its downstream signaling pathways are potentially helpful and novel tools to counteract and fight breast cancer. However, recent advances in our understanding of ERS are focused on characterizing and modulating ERS between healthy and disease states, and so little attention has been paid to studying the role and clinical application of targeting ERS in a certain cancer. In this review, we summarize the function and main mechanisms of ERS in different molecular types of breast cancer, and focus on the development of agents targeting ERS to provide new treatment strategies for breast cancer. Video Abstract